Development and validation of a TRACE/PARCS core model of Leibstadt Kernkraftwerk cycle 19. (March 2017) - Hursin, M.; Bogetic, S.; Dohkane, A.; Canepa, S.; Zerkak, O.; Ferroukhi, H.; Pautz, A.
Highlights: Development of a TRACE/PARCS plenum to plenum model for the Swiss BWR Leibstadt (KKL). Systematic comparison of the TRACE/PARCS and SIMULATE-3 for a simplified BWR model. Satisfactory verification of the TRACE/PARCS KKL model against SIMULATE-3. TRACE/PARCS and SIMULATE-3 showed similar discrepancies compared to plant data. Abstract: The paper deals with the development of a TRACE/PARCS plenum to plenum model for the Swiss Boiling Water Reactor (BWR) Leibstadt (KKL), for cycle 19. It summarizes a verification of the model against an existing SIMULATE-3 model and a validation against Travelling Incore Probes (TIP) at various points of the cycle 19. First, the TRACE/PARCS agreement with SIMULATE-3, for a simplified BWR reactor is analysed. The discrepancies are less than 300 pcm in terms of keff, 6.5% axially and 2% radially in terms of nodal power prediction across the reactor cycle. The discrepancies are due to the mapping of the cross sections when considering the complex default branch/history structure of CASMO-4; and to the modelling of the vessel in TRACE, the solution of the heat conduction in the fuel and the evaluation of the bypass flow. When the KKL cycle 19 model is considered, the TRACE/PARCS agreement with SIMULATE-3 is satisfactory, in terms of keff with discrepancies less than 700 pcm across the reactor cycle; and in terms of Relative Power Fraction (RPF) as well, with discrepancies less than 9% axially and 2% radially, across the reactor cycle. Finally, when comparing to TIP measurements, the TRACE/PARCS methodology and models showed some similar discrepancies than SIMULATE-3, as long as the detector model is not used. When using its detector model to predict the TIP response, TRACE/PARCS shows larger discrepancies with TIP measurements.